Detecting peat degradation using low altitude remote sensing technologies - Chauke, Mathapelo Petunia (My University, 2021)
Peatlands are rare and unique in South Africa ;they occur in patches and stripes at the valley bottom. They are mostly found in the wet eastern and southern parts of the country and are characterised as groundwater-dependent ecosystems. South Africa's peatlands are at risk as a result of improper management and use. These include growing population demand for pumping of underground water, peat mining, the invasion of infrastructure and species, and agricultural use. Amongst others, these peats are vulnerable to peat fires during extreme drought conditions or after the groundwater level has been artificially lowered/drained. Peat fires are spontaneous ground fires that arise on the floor of forests that produce much heat without flames (smouldering). This research aims to assess peatland degradation using low altitude remote sensing technologies, unmanned aerial vehicles (UAVs) in South African peatlands by: (1) Establishing peat thermal and moisture contents at a small scale, (2) Identifying peat dryness/peat moisture using TIR and NIR, and (3) Determining the extent of peat fires by integrating multispectral data and investigating thermal anomalies. Remote sensing of peatlands can help develop an understanding of threats to peatlands and treatments to manage them sustainably. It can also help to secure and define areas that are not accessible. Satellite data can help establish the extent of peatlands and the impact of fire disturbance on peatland ecosystems and the atmosphere (smoke affecting the air quality). The study investigated two peat sites (Molopo and Molemane) situated within the hydrological karst region, making them vulnerable to degradation when disturbed by economic activities such as natural resources. Molemane is a peat that has not been significantly affected by the destruction of cultivation/drainage. In contrast, Molopo is peat that a recent forest fire has severely damaged. The results show that the predicted soil moisture has a maximum Perpendicular Soil Moisture Index (PSMI) maximum value of 0.78for Molopo and a maximum value of 0.71 PSMI at Molemane. The results indicate a lower level of peat moisture at the Molopo peat site than Molemane since Molopo is regarded as dry peat. The Temperature Vegetation Dryness Index (TVDI) also points out that Molemane is more pristine than Molopo. Molopo peat has a higher value of TVDI (0.61) than Molemane, which has a 0.51 TVDI average value. PSMI and TVDI have been used to establish maps of peat moisture's spatial distribution across the Molopo and Molemane peat sites. The results from the study showed that: TVDI and PSMI can measure (1) dry area hot spots, which indicated that both PSMI and TVDI can be used for peatland degradation monitoring, although they showed some discrepancies in the spatiotemporal characteristics of peat dryness of the two peat areas; and (2) that ground measured peat moisture had better correlations to PSMI than to TVDI, indicating that there were more statistically significant relationships between PSMI and peat moisture and that PSMI is a more reliable indicator for assessing peat dryness. The study shows that peat moisture is a reliable proxy for peatland dryness level. This proxy can be monitored cost-effectively using UAVs equipped with infrared cameras
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science (Geographical Information Systems and Remote Sensing) at the School of Geography, Archaeology & Environmental Studies, 2021